Lotta al Dopping: An Italian anti-doping campaign - La Torre, A.; Tengattini, M.; Manferdelli, G.; Rotta, A.; Ponchio, D.; Codella, R. (New Studies in Athletics, 2017)
Doping poses a threat to sport worldwide. It puts the user's health at risk, undermines the principle of fair competition and is a demotivating factor for young athletes. Studies have revealed that it is not only affecting professional sportsmen and sportswomen but amateur athletes are also making increasing use of performance-enhancing drugs. Obviously, anti-doping efforts to date have not been completely effective. For these reasons, the Lotta al Doping (Fight Against Doping) project was created with the aim of causing a cultural shift in young people in Italy by taking anti-doping seminars to high schools, first in a single region and later nation wide. Among the initial findings were that young students are unprepared to deal with the doping phenomenon but are potential messengers of a fair philosophy of sport. This study documents the development of the project, which in the 2016-2017 school year reached more than 11,000 students, and the plans for the future. These include training a new cadre of expert seminar leaders to deliver seminars to up to 40,000 students in two years and taking the Lotta al Doping model to other countries, possibly in conjunction with the European Athletics I Run Clean™ e-learning platform.